Agricultural R&D investment intensity: A misleading conventional measure and a new intensity index - Nin-Pratt, Alejandro (Agricultural Economics Research Association, 2021)
The conventional wisdom that developing countries are significantly underinvesting in agricultural research and development (R&D) has been challenged by studies that found that the high rates of return in the literature result from data limitations and inadequate modeling choices. However, evidence of low research effort in developing countries as measured by the intensity ratio (IR)—the percentage of agricultural gross domestic product invested in agricultural R&D—has not been questioned. This article argues that the IR is an inadequate indicator of research effort and proposes an alternative index to measure R&D intensity. Using the proposed index, we find that the investment effort in developing countries is much higher than the one observed when the IR is used, that the contribution of low‐ and middle‐income (LMI) countries to growth in global R&D intensity was higher to that of high‐income (HI) countries in recent years, that the investment gap in LMI countries is close to 50% of R&D investment, and that the proposed development goal of a 1.0% value of the IR is beyond the possibilities of most Asian and African countries.